Fictional games as parody - Rory Summerley (Eludamos, 2025)
This paper conducts a textual analysis of the animated comedic web miniseries Box Peek, analysing it as a general parody of transmedial gaming franchises, particularly the Pokémon TV series. The show features the fictional game of Box Peek, which is used as a device to not only provide drama and motivation for the show’s characters, but also to parody the games and associated conceits that are central to these franchises, often for the sake of humour. This discussion makes use of theories of fiction and parody, cultural analyses of Pokémon and children’s media, as well as Box Peek’s creator’s own commentary to understand how fictional[ised] games create meaning for an audience. It concludes having discussed two major threads of analysis. The first concerning the rules of the game, which implies questions of strategy and technology, which eventually concerns fictional world-building, exploiting the fictional and ludic inconsistencies that exist in transmedial game franchises for humour. The second is the way in which Box Peek, after formally parodying shows like Pokémon, then extends this parody by answering the questions it raises. In so doing it is argued that Box Peek is simultaneously imitating the childlike tone of Pokémon before progressing to a more reflective, adult perspective on the enjoyment of these series by the audience themselves. This leads the (presumed millennial) audience to a retrospective self-assessment of how, now in adulthood, they regard transmedial gaming franchises of their childhood in the late 1990s and early 2000s.